1996
DOI: 10.1074/jbc.271.51.32586
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Tumor Necrosis Factor α and Interleukin 1β in Inducing Transcriptional Down-regulation of Muscarinic M2 Receptor Gene Expression

Abstract: Stimulation of HEL 299 cells with tumor necrosis factor ␣ (TNF-␣) or interleukin 1␤ (IL-1␤) had no effect on M 2 muscarinic receptor expression. However, the combination of these two cytokines markedly down-regulated muscarinic M 2 receptor protein and mRNA expression and uncoupled M 2 receptors from adenylyl cyclase. There was no effect of TNF-␣ and IL-1␤ on the m2 muscarinic receptor mRNA stability, and nuclear run-on assays showed reduced m2 receptor gene transcription. Sequential cytokine addition suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 46 publications
0
29
1
Order By: Relevance
“…However, mechanisms of hyperreactivity 3 days after ozone exposure are not understood. Although IL-1b decreases M 2 receptor expression (56), this is unlikely to explain the ability of the IL-1 receptor antagonist to prevent airway hyperreactivity 3 days after ozone exposure, since we have previously shown that restoring M 2 receptor function at this time point does not prevent airway hyperreactivity (3).…”
Section: Discussionmentioning
confidence: 96%
“…However, mechanisms of hyperreactivity 3 days after ozone exposure are not understood. Although IL-1b decreases M 2 receptor expression (56), this is unlikely to explain the ability of the IL-1 receptor antagonist to prevent airway hyperreactivity 3 days after ozone exposure, since we have previously shown that restoring M 2 receptor function at this time point does not prevent airway hyperreactivity (3).…”
Section: Discussionmentioning
confidence: 96%
“…The muscarinic M 3 receptor expression was increased, whereas muscarinic M 2 receptor (M 2 ) resulted decreased, in induced sputum cells (macrophages, neutrophils, eosinophils) from COPD subjects compared with controls and control smokers (Profita et al, 2005). In this context, it has been observed that cytokines involved in COPD, such as interleukin (IL)-1␤ and tumor necrosis factor (TNF)-␣ (Chung, 2001), are able to downregulate synergistically the M 2 expression in human embryonic lung fibroblasts (HeLa 299 cells), whereas there is no evidence on the role of cytokines in the modification of muscarinic M 1 receptor (M 1 ), M 3 , and ChAT expression (Haddad et al, 1996). Moreover, the role of cigarette smoke (CS) on the expression of ChAT and MRs has to be clarified.…”
mentioning
confidence: 99%
“…IL-1␤ and TNF-␣ are involved in COPD (Chung, 2001) and have been demonstrated to generate a down-regulation of M 2 in human embryonic lung fibroblasts (HeLa 299 cells) (Haddad et al, 1996). Our findings that M 2 expression is reduced in fibroblasts from patients with COPD, compared with control smoker and control subjects, and that TNF-␣ is able to contribute to the M 2 down-regulation are consistent with these observations and support the concept of the involvement of ACh and MRs in the inflammatory processes in COPD.…”
Section: Muscarinic Receptor and Fibroblast Proliferation In Copd 761mentioning
confidence: 99%
“…Significantly higher serum cytokine and salivary levels of messenger RNA (mRNA) for tumor necrosis factor ␣ (TNF␣), interleukin-6 (IL-6), IL-10, interferon-␥ (IFN␥), and lower salivary gland expression of transforming growth factor ␤1 (TGF␤1) have been found in SS patients than in healthy control subjects (2)(3)(4). Additionally, there is a strong rationale for the intervention of each of these cytokines in the pathogenesis of SS (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%